Political parties, business groups, and corruption in developing countries - Yadav, Vineeta (New York Oxford University Press, 2011)
Political corruption is one of the globe's most pressing yet seemingly permanent problems. It is a root cause of low growth and inequality, and plagues numerous nations throughout the world to varying degrees. This book examines corruption levels in sixty-four developing democracies over a twenty-year period.
Keywords: Political corruption -- Developing countries; Political parties -- Developing countries; Business and politics -- Developing countries